The Effectiveness of Bivalent COVID-19 Vaccination: A Preliminary Report - Chen, Ssu-Yu; Lin, Chien-Yu; Chi, Hsin; Weng, Shun-Long; Li, Sung-Tse; Tai, Yu-Lin; Huang, Ya-Ning; Huang, Hsiang; Lin, Chao-Hsu; Chiu, Nan-Chang (Life (Basel, Switzerland), 2023)
Vaccination has been a game-changer in the long battle against COVID-19. However, waning vaccine-induced immunity and the immune evasion of emerging variants create challenges. The rapid-fire development of bivalent vaccines (BVs), comprising ancestral strains and a new variant, was authorized to prevent COVID-19, but the effectiveness of the updated vaccines remains largely unclear. Electronic databases were searched to investigate the immunogenicity and reactogenicity of BVs in humans. As of March 2023, 20 trials were identified. Compared with monovalent vaccination, the induced immunogenicity against ancestral strains was similar. The BVs demonstrated approximately 33–50% higher immunogenicity values against additional variant strains. An observational cohort study showed the additional clinical effectiveness of the BVs. The adverse events were similar. In conclusion, our systematic review found that the BVs had equal immunogenicity against ancestral strains without safety concerns. Approximately 33–50% increased additional antibody titers and clinical effectiveness against additional variant strains were observed in subjects with a BV vaccine with moderate heterogeneity, especially for BA.1-containing BVs.